Avaliação do efeito da eletroestimulação em mulheres com nódulos vocais - Juscelina Kubitscheck de Oliveira Ferreira (2015)
Objectives: To conduct integrative literature review on the use of electrical stimulation for speech therapy and evaluate the effect of transcutaneous electrical nerve stimulation in women with vocal nodules. Method: To perform the integrative review followed the precepts of the Cochrane Handbook and Souza. The question of research that supported the review was: what is the effect of electrical stimulation in the treatment of dysphonia and dysphagia in clinical speech therapy? To select the articles were used databases Medical Literature Analysis and Retrieval System online (Medline), Latin American and Caribbean Health Sciences (LILACS), PubMed and Web of Science / ISI. The criteria for including articles of the integrative review: publications in English, Portuguese or Spanish, with abstracts available in selected databases and which fitted in with the research question in the period 2003-2013. To evaluate the effect of transcutaneous electrical nerve stimulation in women with vocal nodules, 60 women aged 18 to 55 were evaluated. We conducted the assessment of laryngeal image, perceptual voice quality, acoustic analysis, and self-assessment of pre phonation and discomfort after use of transcutaneous electrical nerve stimulation, applied individually and in combination form the language of vibration technique. Thirty participants were assigned to the experimental group 1 (electrical stimulation), 30 in the experimental group 2 (electrical stimulation associated with language vibration) and 30 in the control group consisted of 30 participants of the experimental groups, however, the unit found itself off. Electrical stimulation was applied for 20 minutes. The evaluations were performed by three speech therapists specialize in voice, which should analyze the pre- and post-experiment, noting the proposed results. In self-assessment phonation discomfort the participants noted the degree of vocal effort in pre and after use of electrical stimulation. Results: The literature review article shows that electrical stimulation is a method that brings benefits in the rehabilitation of individuals with dysphagia and dysphonia the speech clinic. As a result there was a decrease in the size of laryngeal lesions, dysphonia degree of improvement, increased TMF and glottal closure with decreased tension of the vocal folds, and decreased muscle electrical activity and pain, being beneficial in improvement in voice quality . Conventional therapy of dysphagia associated with electrical stimulation is beneficial and more efficient than only electrotherapy or conventional therapy and aids in this population rehabilitation process the speech clinic. Transcutaneous electrical nerve stimulation (TENS), applied alone or associated with the language of vibration technique, helps to close the glottis and improves phonation comfort. When TENS is associated with the language of vibration there also improves roughness of voice quality. Conclusion: More research in the speech area is needed to better understand the actual results of electrical stimulation in rehabilitation of dysphonia and dysphagia patients. When applied in women with vocal nodules, TENS application of isolated or associated with the language of vibration technique improves glottal closure and phonation comfort; and when combined with language vibration improves voice quality.